A estética do documentário cinematográfico no cinema contemporâneo de ficção científica: um olhar sobre o filme "Distrito 9" de Neill Blomkamp - Ribeiro, Márcio Almeida (2013)
The purpose of this work is through an analysis of the feature sci-fi movie District 9, by Neill Blomkamp, investigate the use of documentary aesthetic as the proposed narrative for the film, as well as evaluating the choices of the director from the moment it is necessary to replace the documentary style in favor of a traditional narrative film to benefit the film's plot. This duplicity of styles will also be the object of analysis of this study. It will be presented a brief history of cinema, its principal names, as well as the influence of their work in the development of the film industry. We will identify the characteristics of the documentary, the most important filmmakers of this movement and its influence on the development of other movements in film history.